Leveraging the intersectionality of healthcare and hospitality to diversify workforce talent and enhance patient experience - Sven Gierlinger; Nicole Giammarinaro; Mallory Tuomey; Leah Petrosino (The Beryl Institute, 2023)
As healthcare becomes more of a consumerism-based industry, organizations and leaders are embracing innovative approaches and models to drive patient choice and brand loyalty. Northwell Health, New York State's largest comprehensive health system, has integrated hospitality as a core pillar within its dynamic patient experience strategy. This informative case report highlights Northwell's pragmatic approach to designing, implementing, and sustaining an experiential internship program entitled, Hospitality in Healthcare Internship. The program has resulted in action-oriented patient experience performance improvement opportunities as well as create a robust pipeline of hospitality-minded talent into the organization. Experience Framework This article is associated with the Environment & Hospitality lens of The Beryl Institute Experience Framework (https://theberylinstitute.org/experience-framework/). Access other PXJ articles related to this lens. Access other resources related to this lens.